Application of Soil Amendments from Sulfur-Biochar for Greenhouse Gas Mitigation and Increase 2-Acetyl 1-Pyrroline (2AP) of Khao Dawk Mali 105 - Jiaphasuanan, Tassanee; Thongphun , Nittaya (Burapha Science Journal, 2026)
Greenhouse gas mitigation from rice cultivation with increased yield and aroma compound in rice is an important issue for sustainable agricultural development. The influence of biochar containing sulfur was evaluated on greenhouse gas emissions, yield, and 2-acetyl-1-pyrroline (2AP) aroma compound of the Khao Dawk Mali 105 cultivated in rice field located on Srikai Sub-district, Warin Chamrap, Ubon Ratchathani. The experimental design consists of 4 treatments 1) Control (C) no soil amendment/fertilizer, 2) S-biochar1 (S1) added soil amendment of biochar containing sulfur and ammonium sulfate fertilizer, 3) S-biochar2 (S2) added soil amendment of biochar containing sulfur 4) Fertilizer (F) added ammonium sulfate fertilizer as basal and urea as top-dress. Treatments S1, S2, and F were applied with soil amendment or chemical fertilizer in tillering stage (Day 59) and reproductive stage (Day 138). Greenhouse gas emissions (CH4 and N2O) were investigated throughout the cultivation season. The results showed that rice grain yield was significantly increased (P<0.05) by soil amendment of biochar containing sulfur and ammonium sulfate (S1), 665.71 kg/rai, resulting in the total greenhouse gas intensity (GHGI) was smallest, 4.90 kgCO2/kg yield. 2AP in grain were 3.46, 3.35, 3.28, and 3.05 ppm in treatments C, S2, F, and S1, respectively. The issue of increasing aroma compounds in rice will be studied with water management of alternate wetting and drying.